An Evaluation of Relevance of Criminal Intelligence Management and Implications for Security and Public Safety in Benue State, Nigeria - Gberinyer, Justine Tever; Okoro, Ikechukwu; Adishi, Eric (Indonesian Journal of Advocacy and Legal Services, 2022)
The study focused only on five local Government Areas of the State where incidents of various kinds of crime, particularly cattle herders attacks, cattle rustling, armed robbery, banditry, kidnappings and farmers-herders conflicts do occur regularly. A sample size of 18 (n-18) was determined for the study. The interview participants were recruited using the referral approach that was based on the purposive sampling technique of selecting persons with enough stock of knowledge, experience, and expertise on the topic of this study. The participants were recruited from the Nigeria Police, DSS, Nigeria Security and Civil Defence Corps, and community vigilante groups in Makurdi, the State capital located in Makurdi L.G.A (Benue North-west Zone) and four other Local Government Areas , namely, Agatu (Benue South zone), Logo, Kwande, and Katsina-Ala (Benue North-east zone),where all manner of criminal activities, particularly armed robbery, banditry, kidnapping, herders attacks, farmers-herdsmen clashes, and cattle rustling take place on regular basis. Data analysis was done using thematic analysis approach. Lincoln & Guba’s 3-step model was applied with the aid of NVivo 11.The finding of the study was that the management of the collection/collation phase of information meant for intelligence production, including the various agents and tools used for that process (informants, surveillance, technologies (ICT), community policing, and interrogation) predisposes criminal intelligence management to be very relevant to the fight against crime. The finding of the study also showed that how the intelligence analysis phase of the intelligence production process, particularly intelligence analysis is managed makes criminal intelligence management have much relevance and implications to the fight against crime and insecurity.